ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH TERHADAP PELAYANAN BANK SYARIAH KOTA BATAM - NUZUL IKHWAL (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The theme of the article is a business based on the principles of Islamic economics. Perception of service quality is reflected in consumer’s assessment of the realities and expectations of the service he felt. Tangibles, reliability, assurance, responsiveness, and empathy are the five dimensions of service quality. Some 100 respondents were selected as the study sample. Factor analysis techniques as data analysis techniques used in testing the impact of service quality on customer satisfaction on Islamic Bank in Batam. Results of testing of physical evidence, reliability, assurance, responsiveness, and empathy as a dimension of service quality on customer satisfaction in a Islamic Bank in Batam showed a significant positive effect. The result of this test indicates that consumer satisfaction visited Islamic Bank in Batam is affected by quality of service offered.